"I'm valuing the journey as much as the destination": Exploring shared reflection to support novice coach learning. Issue 4 (August 2021) - O'Dwyer, Anne; Bowles, Richard
This paper provides an insight into the trajectory of coach learning over two seasons through a shared reflective process. It describes how a collaborative process in a volunteer, amateur coach setting was supported and sustained. The coach-researchers had coached a university sports team together for two years prior to formalising the collaborative process. They adopted a collaborative self-study methodology to support and structure their reflective practice and learning throughout the study. Weekly individual and collaborative reflections were written by both coaches. They engaged with a critical friend to offer alternative perspectives on their reflections, and they planned their coaching strategies together. This paper illustrates the collaborative reflective process that supported the trajectory of the novice coach learning. This journey is represented using Fuller's concern based model to map concern for self, concern for the task and concern for the learners. The reflective process and learning trajectory are outlined to exemplify the value of informal collaborative reflection to support coach learning. Implications are outlined for shared reflective practice to enhance learning opportunities for other coaching partners and small groups or in other educational domains.